COVID-19 Pathogenesisin the oral cavity: A Review on Oral Impairments and Manifestations - Torgomyan, A.; Saroyan, M.; Hovhannisyan, S.; Mashinyan, K.; Yessayan, L.; Hakobyan, Gagik (Actual Dentistry, 2023)
Abstract. With COVID-19, along with other organ systems, symptoms can also appear in the oral cavity. COVID-19 can cause a number of pathological conditions in the oral cavity of patients, candidiasis, xerostomia, recurrent herpetic lesions, ulcers, vesicles, desquamative gingivitis have been reported, the tongue, palate, lips, gums and buccal mucosa may be affected. Patients with COVID-19 may have difficulty swallowing, burning sensation, most patients have impaired taste and smell. However it is still impossible to draw a clear parallel between the manifestations of dental diseases and the severity of the coronavirus infection, since too little statistical data and clinical observations are available therefore needed for further investigation. The goal of this revue was to compile a list of COVID-19 symptoms in oral tissues and analyze the potential etiopathogenesis that may influence the development of these oral lesions. The key terms were used to search international databases for information. A total of 50 sources on relevant topics were chosen. These preliminary data explain the underlying mechanism oral lesions in Covid-19, and will help on future preventive strategies in clinical practice and in everyday life.